Effectiveness of Using Irrigation Solution to Remove Residues and Smear Layer in Root Canals: Research Using Scanning Electron Microscopy - Kolenko, Ю.; Semenova, І.; Kolesova, Н. (Actual Dentistry, 2025)
Relevance. The widespread prevalence of destructive forms of apical periodontitis, especially among the working-age population, the impact of this pathology on human health, including psycho-emotional status, and the medical and social problems arising from tooth loss as a result of this disease confirm the need to search for new methods of treating this pathology. The study aims to determine the quality of chemo-mechanical treatment of root canals using root canal irrigation with sound activation, as assessed by scanning electron microscopy data. Materials and methods. For this part of the study, 157 patients were examined who, for various reasons (orthodontic, periodontal), were scheduled for tooth extraction. Forty teeth were selected for the study. According to the standard instrumental treatment technique (apical-coronal or coronal-apical), the root canals of the teeth were treated in a series of experimental studies using a 6% sodium hypochlorite solution and ozonized water. An ultrasonic endoactivator (Dentsply) was employed for 1 minute. Electron microscopic studies were performed using scanning electron microscopy. The processing and analysis of the obtained data were performed using the “Statistics 16.4” statistical software package. Results. After instrumental treatment of root canals with a 6% sodium hypochlorite solution and ozonized water, the contaminated layer is also reliably removed from the walls of the root canals. Most of the dentinal tubule openings are open. However, often, crusts and residues of the contaminated layer remain. The additional use of Endoactivator (Dentsply) with ozonized water enables more effective treatment of root canals. In particular, more reliable opening of the dentinal tubules is achieved throughout the entire length of the root canal: in its apical, middle, and coronal parts. Using an improved irrigation technique, it was possible to achieve significantly better results in cleaning the root dentine, with a mean improvement of 1.32 ± 0.16 points. Conclusions. Morphological studies have shown that endodontic treatment of root canals using a 6% sodium hypochlorite solution, ozonized water and under the action of an ultrasonic Endoactivator (Dentsply) for 1 minute, a more reliable opening of the dentinal tubules is achieved throughout the entire length of the root canal: in its apical, middle and apical parts. The proposed method of chemical-mechanical root canal treatment enables the effective cleaning of root canal walls by 1.29 ± 0.13 points, as classified by Mahmoud Torabinejad and Abbasali Khademi, p < 0.1. The proposed method is effective in cleaning the apical part of the root, 1.71 ± 0.38 points at p < 0.1.